1990
DOI: 10.1099/00207713-40-4-379
|View full text |Cite
|
Sign up to set email alerts
|

Erwinia persicinus, a New Species Isolated from Plants

Abstract: Five strains of a gram-negative, oxidase-negative, facultatively anaerobic, fermentative, motile, rod-shaped bacterium with the general characteristics of the family Enterubucteriaceae were isolated from tomatoes (three strains), a banana, and a cucumber. All of the strains produced a water-soluble pink pigment. As determined by DNA hybridization (hydroxyapatite method) these five strains were 85 to 100% related in 60 and 75°C reactions, and related sequences exhibited 1 % or less base sequence divergence, ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…Most members of this genus characteristically cause diseases of plants, vegetables, and fruits (31). The phylogenetic position of the genus Erwinia, along with other members of the Enterobacteriaceae associated with plants, have been explored by using 16S ribosomal DNA sequence comparisons (10,11). Four phylogenetic groups, each representing a branch of a lineage, have been proposed (31).…”
mentioning
confidence: 99%
“…Most members of this genus characteristically cause diseases of plants, vegetables, and fruits (31). The phylogenetic position of the genus Erwinia, along with other members of the Enterobacteriaceae associated with plants, have been explored by using 16S ribosomal DNA sequence comparisons (10,11). Four phylogenetic groups, each representing a branch of a lineage, have been proposed (31).…”
mentioning
confidence: 99%
“…However, E. rhapontici has been reported to be a causative agent of rhubarb crown rot, pink grain of wheat strains, and pink seed of pea (27,41). Based on 16S rDNA sequence studies, E. rhapontici has been found to be very similar to the type strain of Erwinia persicinus (99.0%), found in vegetables and fruits (21,27).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, a case of contact lens-related infectious keratitis was attributed to R. radiobacter (Fenner et al, 2019). The plant pathogen Erwinia persinicus was originally isolated from tomatoes, cucumber and banana (Hao et al, 1990) and was found to infect bean pods and seeds. E. persinicus also exhibited pathogenicity in invertebrate model infection stems such as Caenorhabditis elegans and Drosophila melanogaster (Starr and Chatterjee, 1972;Chatterjee and Starr, 1980;O'Hara et al, 1998).…”
Section: Bacterial Phytopathogensmentioning
confidence: 99%